Phygitalization of stores in Africa: a potential to be developed - (:unkn) unknown (My University, 2024)
The integration of technologies at the point of sale has created phygital. Batat (2022), defines it as a holistic ecosystem combining the physical and the virtual, aimed at enhancing the customer experience. A review of the literature, reveals that only one study addresses phygital stores in Africa, specifically in Algeria (Meradi and Abdelhak, 2020), but it is based on a netnographic study of a mobile application, in contradiction with Yao et al.'s (2024) conclusion that e-commerce platforms, flyers and apps are not synonymous with phygital. The aim of our study is to understand the barriers to the adoption of phygital technologies in Africa. To this end, we mobilized secondary data from articles, books and reports. We followed a thematic analysis to identify four main barriers: economic, technological, social and ethical.
Keywords: African Research